Undifferentiated high-grade sarcoma with UES-like features in the retroperitoneum: a Case Report with TP53 p.R306 mutation - Zhu, Yinan; Sun, Mingfang; Wang, Ziyue; Lin, Xuyong (Frontiers in Oncology, 2025)
Undifferentiated embryonal sarcoma(UES) is a rare, highly malignant tumor mainly originating from the liver, composed of primitive undifferentiated mesenchymal cells. Undifferentiated embryonal sarcoma of the liver(UESL) is a rare entity. Here, we report a case of abdominal mass in a young female that morphologically resembles UES without liver involved. Notably, the mass was located from the abdominal cavity to the retroperitoneum without any correlation with the liver. The patient had no history of prior tumors, and detailed examinations of the liver revealed no definite lesions. In addition, we propose undifferentiated high-grade sarcoma with UES-like features in the retroperitoneum, in which TP53 gene mutation may serve as the initiating factor for tumorigenesis.